THE PORTRAYAL OF ISLAMIC VALUES AND PERSPECTIVE OF BUGIS – MAKASSAR CULTURE IN THE CONCEPTION OF DOWRY FOR PEOPLE IN BANGKALA VILLAGE, MAKASSAR, SOUTH SULAWESI - Said, Irwanti (Jurnal Adabiyah, 2022)
This research is about the conception and practice of dowry for people in Bangkala village, and how it portrays the Islamic perspective of Bugis-Makassar culture. Researchers took two formulations of problems that will be discussed in this study. First, what is the conception and practice of dowry in Bangkala village? Secondly, how does the conception of dowry for Bangkala people portray the Islamic perspective and values and the richness of Bugis–Makassar culture? The type of research used is qualitative research with social welfare and sociological approach methods. The results of this study illustrate the conception of dowry in Bangkala village. Dowry determines the implementation of marriage. The Dowry (Mahar) is a form of absolute obligation by the male side to the female side. This is in line with the view in Islam that the dowry is a pure right of women, which is recommended to be given to them as an expression of men's desire for their future wives. The Dowry conception for the Bangkala people also portrays how the social stratification in Bugis – Makassar culture, also plays a big role in determining the amount and types of dowries given to the bride in Bangkala village wedding ceremonies. The dowry is not only a sign of the future husband's love and affection for the proposed wife, but it is also an appreciation symbol for the bride and her family in terms of their social stratification in the local society. ملخص يدور هذا البحث حول معنى المهر في عادات زواج ماكاسار بوغيس في قرية بانغكالا في منطقة مانغالا في مدينة ماكاسار. أخذ الباحثون صيغتين للمشاكل التي سيتم مناقشتها في هذه الدراسة. أولا، كيف يعني الوخز للأسر النسائية في جمارك ماكاسار في قرية بانغكالا في منطقة مانغالا بمدينة ماكاسار، وثانيا، ما هي أشكال المهر للأسر النسائية في جمارك ماكاسار في قرية بانغكالا في منطقة مانغالا، مدينة ماكاسار. نوع البحث المستخدم هو البحث النوعي مع أساليب نهج الرعاية الاجتماعية وعلم الاجتماع. توضح نتائج هذه الدراسة حول معنى المهر في قرية بانغكالا بمقاطعة مانغالا بمدينة ماكاسار، أن معنى المهر يحدد تنفيذ الزواج، حيث يعتبر المهر شكلا من أشكال الالتزام المطلق من جانب الرجل تجاه الجانب الأنثوي، وهذا يتماشى أيضا مع الرأي السائد في الإسلام بأن المهر حق خالص للمرأة التي يوصى بإعطائها للمرأة تعبيرا عن رغبة الرجل في زوجاتها المستقبليات، وتعتبر من علامات الحب والمودة لزوج المستقبل للزوجة المقترحة.